Spanish pluperfect indicative in contact with three Native American languages - Blestel, Élodie (Lenguas Modernas, 2011)
Some Latin American diatopic occurrences of the Spanish pluperfect indicative differ from the traditional uses of this tense –namely, the expression of an action in the past that occurred before another action in the past –. These occurrences can express mirativity or evidentiality, which are semantic categories present in the adstratic languages of those areas (the Quechua and Aru families in the Andean area, and Guarani in Paraguay). Although these cases have been regarded as effects of cross-linguistic influence, we must also look for the internal causes that allow such convergence. In this paper, we revisit those diatopic occurrences and argue that it is the cognitive operation involved in the use of pluperfect in language which allows not only the emergence of such discursive occurrences in American Spanish, but also their use and coexistence with more canonical uses of that tense.